Genetic markers in methotrexate treatments. Issue 6 (December 2018) - Giletti, Andrea; Esperon, Patricia
Abstract Methotrexate (MTX), a structural analog of folic acid, is widely employed in the treatment of different cancers and autoimmune diseases. Despite the successful results observed, the main disadvantage lies in interpatient variability in the pharmacokinetic and pharmacodynamic parameters. In particular, adverse events and toxicities induced by MTX are a matter of concern and can be the cause of dose reduction or treatment discontinuation. Among the different approaches to reduce MTX therapeutic limitations, pharmacogenomics contributes by considering the effect of inherited genetic differences on those parameters. This review provides an update on MTX pharmacogenomics. It reports the contribution of main gene polymorphisms involved in the influx, efflux, cellular effect, and elimination on MTX toxicity and efficacy, on all the diseases treated with this drug. From the analysis of the data presented in this review, we concluded that only gene polymorphismsMTHFR rs1801133, SLC19A1 rs1051266, andTYMS rs34743033 could influence clinical decision-making.